Modeling the construction of an efficient customer club for the quantitative and qualitative development of increasing customers in the banking system - Ali Taher khani kojariha; Younos Vakil Alroaia (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of the current research is to find a model to build an efficient customer club for the quantitative and qualitative development of increasing customers in the banking system. According to its purpose, the research method is a\applicable; and in terms of implementation method, it is mixed (qualitative-quantitative); and exploratory in terms of the research implementation strategy. The statistical population in the qualitative section includes 11 specialists and experts, managers, and vice-presidents of the bank, and experts in the field of management model and customer club, selected through purposeful sampling and snowball; and the statistical population in the quantitative section includes 385 people from all members of the Saderat Bank's customer club, selected using Cochran's formula as a sample and by simple random sampling. Data collection tools include semi-structured interviews and researcher-made questionnaires in the quantitative section. In the data analysis, using the theme analysis approach, MAXQDA10 software was used in the qualitative part, and SPSS and AMOS software were used in the quantitative part. The results in the qualitative part showed that 93 open codes, 52 sub-themes, and 6 main themes were identified from the interviews in the form of the dimensions of the efficient customer club building model; and the results of the quantitative part showed that the identified components have an explanatory and meaningful effect on the construction of the efficient customer club in the banking system in the direction of quantitative and qualitative development of customer increasing. Extended Abstract Introduction Customer is the most important asset and tool related to the profitability of an organization (Saprianto et al, 2021). Attention to the customer is so important that the success of an organization and structure is evaluated in customer satisfaction (Javad et al, 2021; Son et al, 2021). Customer satisfaction is an index directly related to the issue of customer loyalty, and loyalty is the most important issue in relation to profitability and business success based on the creation of perceived value for the audience (Patma et al, 2020; Jain et al, 2015). The issue of business and customers is a multifaceted structure related to many variables that involves different organizations in different dimensions (Pollak et al, 2022; Raza et al, 2022). In this context, different business organizations use specific strategies to increase income and business success in order to create maximum profit and financial and income capability (Federo & Carranza, 2016). Therefore, as it is clear in the current situation, identifying customer behavior and their interests and views is very important and necessary in commercial success and economic competition. The basic goal in this field is to apply a tool to change and identify the interests and tastes of the customer in order to gain power and make fundamental changes in this field (Solomon, 2013). A comprehensive review of the studies conducted in the field of building a banking customer club indicates that the identification of the dimensions of the comprehensive model is very effective in identifying the factors of building an efficient customer club for the quantitative and qualitative development of customer growth in the banking system; on the other hand, the novelty of the topic of building an efficient customer club, the generalization of the research done in this field, and the lack of a suitable model for building an efficient customer club prompted the researcher through acquiring sufficient knowledge in the above field and applying the knowledge and experiences of academic consultants and bank managers; to explore the dimensions of building an efficient customer club in order to identify the dimensions and indicators of a comprehensive model for building an efficient customer club, and to answer this key question for us, which is: how is the model of building an efficient customer club for the quantitative and qualitative development of increasing customers in the banking system? Literature The importance of the customer Customer and understanding its behavior are the most important assets of the organization in business success and related patterns, and companies in relation to people look for their most important program on this index and its achievement (Bryan et al, 2017); In other words, the sale of the product and the use of services and success in the competitive and economic market depend on attracting customers and maintaining the customer's trust in the desired product. Different business organizations use specific strategies to increase income and business success in order to create maximum profit and financial and income capability; therefore, as it is clear in the current situation, identifying customer behavior and their interests and views is very important and necessary in commercial success and economic competition (Federo & Carranza, 2016).